FACTORS IN SHAPING AN UNCOMPROMISING MORAL POSITION AGAINST CORRUPTION AMONG STUDENTS - Khamidov Mansurjon Abdukhalilovich (New modern researchers: modern proposals and solutions, 2025)
This article examines the psychological, pedagogical, and social factors that contribute to shaping an uncompromising moral stance against corruption among young people. Based on the concepts of social perception, moral consciousness, value systems, and social motivation, the study emphasizes the necessity of developing anti-corruption immunity in students. The role of family, educational environment, personality socialization, and cognitive mechanisms in forming attitudes toward corrupt behavior is also discussed. The findings highlight the psychological roots of corruption, explaining the phenomenon through cognitive dissonance, social norms, and personal responsibility. The paper underlines that fostering values of justice, integrity, and social responsibility in youth is a key direction to ensure a stable psychological position against corruption.